2009
DOI: 10.1159/000264269
|View full text |Cite
|
Sign up to set email alerts
|

Optical Online Monitoring of Uric Acid Removal during Dialysis

Abstract: This study estimates the total removal of uric acid (TRUA) by online UV absorbance measurements in the spent dialysate in two different dialysis centers in Estonia and Sweden. Sixteen dialysis patients were included. All dialysate was collected that gave the reference for TRUA. Two regression models were investigated: one for each patient (UV1) and one for the entire material (UV2). TRUA from the three methods was in the same order but showed a statistically significant differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…In those previous studies, concentrations and UV absorbance were utilized to estimate total removal of the particular solute [15,16]. As in other studies [9], our study showed a different appearance of the elimination curve for phosphate than urea and uric acid.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…In those previous studies, concentrations and UV absorbance were utilized to estimate total removal of the particular solute [15,16]. As in other studies [9], our study showed a different appearance of the elimination curve for phosphate than urea and uric acid.…”
Section: Discussionmentioning
confidence: 50%
“…drain tube) of the dialysis machine, as in earlier studies [15,16,17], with all spent dialysate and ultrafiltrate passing through a rectangular optical flow cuvette (JASCO) with a path length of 10 mm. To find out if it would be possible to create a specific single-wavelength model for phosphate similarly to an earlier study [17], a single wavelength of 297 nm was selected using a bandwidth of 2 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that a model, which uses dialysate values, could receive values from an optical monitoring system [20][21][22][23], enabling continuous monitoring of the dialysis efficacy and prognosis for patient's outcome. Optical monitoring of the urea based dialysis dose is considered as a valid and beneficial alternative to the existing methods [24].…”
Section: Discussionmentioning
confidence: 99%
“…The wavelength of 280 nm is commonly used in optical dialysis adequacy sensors for this purpose [10] and UA appears to be the main chromophore at this wavelenth among variety of metabolites, eliminated from the blood of end-stage renal disease (ESRD) patients by dialysis [11]. The decline of the absorbance of spent dialysate at 280 nm during dialysis session reflects quite well the removal of all small water-soluble uremic toxins and PAR with its absorbance maximum near 254 nm do not seem to substantially interfere with optical monitoring of elimination of this group of solutes from the blood of patients with end-stage kidney disease [12].…”
Section: Introductionmentioning
confidence: 99%